Development of a Visual, Auditory and Kinesthetic (VAK) Model-Based Classroom Management Toolkit for Pre-Service Teachers - Mugot, Maria Angelica C. (ASEAN Journal of Education, 2019)
Classroom management is essential in students’ learning. This embedded mixed study intended to develop a classroom management toolkit for pre-service teachers based from Fleming’s (2001) visual, auditory and kinesthetic (VAK) model. The activities were designed to pre-service teachers teaching Preschool to Grade 3 classes. In developing the toolkit, Analysis, Design, Development, Implementation and Evaluation or ADDIE model was used. The evaluation of implementers and experts was done through the use of the researcher-modified VREP by Simon and White (2011). Descriptive statistics was used to treat the data gathered. The general findings showed that the toolkit “exceeds the expectations” of the implementers and majority of the implementers found the toolkit “effective”, “useful” and “helpful.” From the findings of the study, it is, thus, recommended that higher educational institutions that train pre-service teachers may utilize the developed VAK model based-classroom management toolkit. Moreover, teachers in early childhood may use the toolkit. Future studies may be planned out for the improvement in terms of more classroom management strategies in the VAK model-based classroom management toolkit for pre-service teachers.